2001
DOI: 10.2466/pms.2001.93.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Examination Performance and Graphological Analysis of Students' Handwriting

Abstract: Research has yielded mixed support for graphological claims. The present study was designed to see whether specific components of students' handwriting were related to personality traits associated with achievement in written examinations. If aspects were identified that could be used to predict future academic performance, the findings would not only be of interest to graphologists but would be invaluable to both student and tutor in a teaching environment. In a blind trial, 100 handwriting samples from first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…8,9 Graphology, the study and analysis of handwriting and its relation to human behavior, has largely been disproved and is considered a pseudoscience by most. [10][11][12] Most behavioral research originated in the analysis of verbal speech, with several large studies demonstrating a relationship between distinct behavioral traits and word choices in spontaneous verbal speech. 13 From these emerged a rational but intriguing correlation between egocentrism and use of the personal pronoun ''I.''…”
Section: Background and Purposementioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Graphology, the study and analysis of handwriting and its relation to human behavior, has largely been disproved and is considered a pseudoscience by most. [10][11][12] Most behavioral research originated in the analysis of verbal speech, with several large studies demonstrating a relationship between distinct behavioral traits and word choices in spontaneous verbal speech. 13 From these emerged a rational but intriguing correlation between egocentrism and use of the personal pronoun ''I.''…”
Section: Background and Purposementioning
confidence: 99%
“…There are several individual reports of residency programs using ''I'' counts from personal statements in an attempt to identify selfish or egocentric behavioral traits among applicants. 11 In addition, a multitude of online and printed resources warns applicants of the social dangers associated with liberal use of the ''I statement,'' demonstrating the pervasive cultural aversion to this pronoun. [12][13][14][15] The purpose of this retrospective study Background The admissions process for residency encompasses numerous objective and subjective measurements by which an applicant is evaluated.…”
Section: Background and Purposementioning
confidence: 99%
“…Oosthuizen (1990) analyzed the correlation of questionnaire and graphological indices with learning and achievement and found that graphology better predicts those scores than questionnaires. Also Lowis and Mooney (2001) assessed the conjunction of graphology with the achievement of students and found that the individual feature slant can predict achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that handwriting influences reading, writing, language and critical thinking . Children with writing disorders have a tendency towards lower mathematics achievement, low verbal IQ, and increased attention difficulties, and consistently achieve lower marks compared with controls . Handwriting difficulties in children include illegibility and inefficient writing speed.…”
mentioning
confidence: 99%